Sistem Pendukung Keputusan Dalam Menentukan Karyawan Terbaik Dengan Menggunakan Metode Simple Additive Weighting (SAW): Decision Support System for Determining the Best Employees Using the Simple Additive Weighting (SAW) Method - Astuti, Rini Widya; Rohman, Abdul (Technomedia Journal, 2024)
Increasing standards in the employee selection process by the Company's Human Resources Division has encouraged employees to continue improving their abilities. To evaluate employee performance effectively, a system is needed that can provide an objective assessment of their performance. This aims to ensure that the assessment carried out by the company on the competence and quality of employees is in accordance with existing needs. Therefore, developing a Decision Support System is very important to provide solutions and assistance to Human Resources Managers in selecting the best employees at PT. Sam Kyung Jaya Garments. The Simple Additive Weighting (SAW) method was chosen as the approach used in this system. The SAW method is a method that calculates the total weight of the performance assessment for each alternative for all relevant attributes. It is hoped that the results of this system can provide useful options for the Human Resources Division in determining the best employees in the company.